Major challenges made to the Malaysian Constitution in the court of law. 1957 – 1985 / Salmah Sharif - Sharif, Salmah (Faculty of Law, 1985)
Malaysia as a political entity come into existence on 16th September 1963 but the existence of constitution as the highest law of the country that bound everybody is much more earlier than that, that is when Malaya become independent in 1957. This mean that our constitution is a historic form or written document which has culmination of historical process where we fought against the British Government for our right and freedom such as political independence, self-government , democracy and civil liberties and economic well-being which as a result these rights are expressly conferred in our constitution. Constitution is an ideal concept of law which guide the men how the country should be ruled and it also with its provision make this country a batter place to which the individual and multi religious society to live.